1988
DOI: 10.1049/ip-d.1988.0057
|View full text |Cite
|
Sign up to set email alerts
|

Silicon flow sensors

Abstract: A short review is given of the principles of thermal flow sensors in silicon. Sensor structures based on the thermal anemometer principle are discussed, as are the integrated flow sensors developed at Delft University of Technology which use the detection of an onchip temperature difference. Recent research on one-and twodimensional sensors for the measurement of both flow magnitude and direction are presented, including experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…1 variety is given in [1]. There it is shown that such sensors obey the following relationship, known as King's law [11] (1) where is the total power dissipated in the heaters, is the overheat with respect to ambient temperature, and is the flow velocity.…”
Section: Ambient-temperature Compensationmentioning
confidence: 99%
See 4 more Smart Citations
“…1 variety is given in [1]. There it is shown that such sensors obey the following relationship, known as King's law [11] (1) where is the total power dissipated in the heaters, is the overheat with respect to ambient temperature, and is the flow velocity.…”
Section: Ambient-temperature Compensationmentioning
confidence: 99%
“…The layout of a typical integrated 2-D thermal flow sensor is shown in Fig. 1 [1]- [4]. It consists of a square silicon chip (or membrane) in which a diode, four thermopiles, and four resistive heaters are integrated.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations